Risk factors of Gestational Diabetes Mellitus Among Saudi Women - Rahim, Somia K A.; Saeed, Osman Kh; Mirghani, Omer A. (مجلة الجزيرة للعلوم الصحية; مجلد 12 عدد 1 (2016), 2016)
Abstract: Objective: The aim of this study was to identify the main risk factors of Gestational Diabetes Mellitus among Saudi women. Methodology: This is a case control laboratory-based study conducted in Wadi Al Dawasir City in Saudi Arabia.600 pregnant women as follows; 300 screened pregnant women as the study group and 300 non screened pregnant women as the control group.Selection Criteria for the screened group: Should be booked at 28 weeks or before that, not known to be diabetic before pregnancy or diagnosed as cases of GDM before 24 weeks. Selection Criteria for the non-screened group: They were not diagnosed before pregnancy as cases of DM or diagnosed during pregnancy as cases of GDM.Screening for GDM: Screening for GDM was a routine using loading dose glucose (LDG) or glucose challenge test (GCT) between 24-28 weeks gestation according to the hospitals protocol. The pregnant women were classified into high risk or low risk according to the following characteristics  Results: Risk factors in the screened mothers with positive LDG result was: family history was identified in 56.1% (23/41) of mothers and it was absent in 43.8% (18/41). The next main risk factor among the mothers with positive LDG results was a history of baby weight 4 kg or more and was found in 9.76% (4/41) followed by history of intrauterine fetal death that was detected in 7.32% (3/41). Only one mother 2.44% (1/41) had past history of gestational diabetes mellitus similar to mothers with history of babies with congenital malformation that was detected in 2.44% (1/41) also. Family history was the main risk factor among mothers with positive LDG results as it was found in 56.1%. Within the 20 mothers with significant oral glucose tolerance test (OGTT) results, 80% (16/20) had risk factors and 20% (4/20) had no risk factors. Conclusion: Identifying of risk factors is important for screening for GDM but even women with low risk and no risk factors should be screened for GDM.